Vortex motion in an acoustic chamber - Mohd. Ghazali, Normah (Penerbit UTM, 2007)
The field of thermoacoustics basically involves the interaction of acoustic waves and solid boundaries. Expansion and compression of fluid particles in acoustic waves are generally followed by temperature oscillations. These oscillations of fluid particles when in contact with solid boundaries can generate powerful and useful thermodynamic effects - acoustic power. Sound waves encountered in our daily life produce this same effect but the order of magnitude is generally too small to be noticed. Today’s widely accepted definition of the phenomena, however, can be classified into (i) a temperature gradient-induced oscillations, and (ii) temperature gradient induced by oscillations. The first is found in a thermoacoustic heat engine, a prime mover that operates as that taught in an introductory thermodynamics course. Power is generated in the form of sound waves as heat is transferred from a high-temperature reservoir to a low-temperature reservoir. This is achieved through a temperature gradient across heat exchanging plates within a stack that is externally connected to the heat reservoirs. The flow of heat and work is reversed in the thermoacoustic heat pump or refrigerator. Work input in the form of acoustic waves generates a temperature gradient across the stack as transfer of heat from a low-temperature to a high-temperature reservoir occurs.